2017
DOI: 10.1111/jsr.12555
|View full text |Cite
|
Sign up to set email alerts
|

Dream emotions: a comparison of home dream reports with laboratory early and late REM dream reports

Abstract: SUMMARYThe aim of this study was to compare the emotional content of dream reports collected at home upon morning awakenings with those collected in the laboratory upon early and late rapid eye movement (REM) sleep awakenings. Eighteen adults (11 women, seven men; mean age = 25.89 AE 4.85) wrote down their home dreams every morning immediately upon awakening during a 7-day period. Participants also spent two non-consecutive nights in the sleep laboratory where they were awoken 5 min into each continuous REM sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
3
23
0
1
Order By: Relevance
“…Moreover, here we show that the mDES may be a useful and reliable tool to investigate dream emotionality. The mDES, in fact, has been very seldom used in dream research-with Sikka et al’s work [ 26 , 43 , 44 , 46 , 51 ] being, to our knowledge, the only case, whereas most of the studies exploited instruments addressing narrower sets of emotions or ad hoc scales lacking validation (e.g., [ 27 , 41 , 42 , 45 ]). We believe that the use of a broader array of emotion items appears particularly appropriate in investigating dream emotionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, here we show that the mDES may be a useful and reliable tool to investigate dream emotionality. The mDES, in fact, has been very seldom used in dream research-with Sikka et al’s work [ 26 , 43 , 44 , 46 , 51 ] being, to our knowledge, the only case, whereas most of the studies exploited instruments addressing narrower sets of emotions or ad hoc scales lacking validation (e.g., [ 27 , 41 , 42 , 45 ]). We believe that the use of a broader array of emotion items appears particularly appropriate in investigating dream emotionality.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to note that a main limitation of research on dream emotions may be linked to the use of numerous different instruments for the collection of dream emotion ratings and to the constraints of the most common available scales, such as the POMS (Profile of Mood States [ 49 ]), which is limited to maladaptive affective states, or the PANAS (Positive and Negative Affect Scale [ 50 ]), which includes positive emotions but exclusively targets high activation affective states. Instead, the mDES, which has seldom been used in dream research [ 26 , 43 , 44 , 46 , 51 ], reduces the risk of underestimating the presence of positive emotions, since it includes a more balanced number of positive and negative items (ten positive and ten negative in the original versions [ 47 , 48 ], twelve positive and ten negative in our Italian version).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because the current study was performed in the laboratory environment, the findings may have been influenced by the experimental setting and procedure. For example, it has been shown that home dream reports contain more negative affect, especially fear, than laboratory dream reports (Foulkes, 1979;Sikka et al, 2018). As such, it would be important to repli-cate the study in a more naturalistic home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because the current study was carried out in the laboratory environment, the findings may have been influenced by the experimental setting and procedure. For example, it has been shown that home dream reports contain more negative affect, especially fear, than laboratory dream reports (87,88). As such, it would be important to replicate the study in a more naturalistic home environment, although currently the technology needed for conducting such a study is still under development.…”
Section: Discussionmentioning
confidence: 99%